Public Service Quality to Improve Public Satisfaction in Religious Affairs Office, Cilawu District, Garut District - Muhammad Naufal, Ilham; Maesaroh, Imas (Proceedings of International Conference on Da'wa and Communication, 2021)
The purpose of this research is to find out the types of public services in the Cilawu District Religious Affairs Office, to understand the pattern of service used in the Cilawu District Religious Affairs Office, to identify factors that are influencing the quality of public services, and to analyze the quality of public services in the Cilawu District Office of Religious Affairs using the SERVQUAL method. This research shows that the Cilawu District Religious Affairs Office offers governmental, public, and general services to the public. Also, the pattern of service used in the Cilawu District Religious Affairs Office is the old public administration. Next, factors that influence the quality of public services in the Cilawu District Office of Religious Affairs are work motivation, communication skills, work experience, responsibility, leadership, and work environment. Lastly, the service quality at the Cilawu District Religious Affairs Office is good since the five aspects of SERVQUAL have positive feedback from the public.